Systematic Literature Review (SLR): Mendeley Sebagai Solusi Untuk Permasalahan Penyusunan Daftar Pustaka di Kalangan Mahasiswa - Nurazizah Dawamah; Usiono Usiono (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
An obstacle that students often face when they write scientific papers is the bibliography, which must be done to avoid plagiarism. Due to the large number of references that students need when writing scientific papers, some students will find it difficult to make it manually. Therefore, the Mendeley application is needed to facilitate the preparation of the bibliography automatically. Many students do not know how to use the Mendeley application and do not even know how to use it. This training is held online through the Zoom application and is aimed at general students who want to learn to use a practical application called Mendeley to create an automatic bibliography. The training is a collection of activities that aim to help students manage their references independently. Thus, the quality of education in Indonesia is also expected to improve. The expected results of this training are an increase in participants' knowledge and understanding of the use of the Mendeley application and an increase in participants' skills in using the application to complete various forms of scientific writing, such as journals, theses, and final assignments.